A study on comparative colour fading in daylight and xenon arc lamp. (6th November 2018) - Roy Choudhury, Asim Kumar; Chatterjee, Biswapati
Abstract : Purpose: The purpose of this paper is to compare light fastness assessments by exposure of fabric dyes with various dyes in daylight and an artificial xenon arc lamp. Design/methodology/approach: Cotton fabric dyed with 66 reactive, vat, azoic and direct dyes dyed in different depths were exposed to daylight and Xenon arc lamp for assessment of light fastness by standard methods. The light fastness rating and fading hours by the two methods were analysed and compared statistically. Findings: The correlation between the corresponding light fastness rating (LFR) measured in Xenotest and daylight is quite high (0.93). The logarithmic correlation coefficients between fading hour (FH) and LFR in Xenotest and daylight are 0.95 and 0.88, respectively. For Xenotest, the assessed LFRs are same as those predicted from geometric progression up to LFR of 5.5, and thereafter, the former is higher. On the other hand, in the case of daylight, the assessed LFR is lower. Assessments for three successive seasons showed high repeatability in case of Xenotest and moderate repeatability in case of daylight. Assessments for three successive seasons showed high repeatability in case of Xenotest and moderate repeatability in case of daylight. Research limitations/implications: The exposure conditions in daylight cannot be controlled or standardised, whereas the exposure in Xenon arc lamp in the accelerated fading instrument can be strictly controlled. These differences in exposure control may affect the repeatability of experimental findings. Practical implications: Inconsistent ratings may be because of little deterioration of samples during storage, as well as seasonal variation of daylight. Social implications: There are no direct social implications. Originality/value: The researches on the comparison of the two light fastness assessment methods have not been reported in any recent publication to the best our knowledge.